Mental Structure of Assessment and its Hierarсhiс Structure - Prokhorova, Olga N.; Chekulai, Igor V.; Baghana, Jerome; Kuprieva, Irina A.; Pugach, Vladimir S. (Journal of History Culture and Art Research, 2018)
This article describes the conceptual basis of formation of the mental structure of assessment. As it is stated in the ongoing research, the structure consists of obligatory and optional elements which constitute a hierarchy. To prove this fact, special attention is given to the conceptual features of these elements, their content and correlation with the object of reality. Considering the mental structure under study as a structure with transparent borders, we pay particular attention to the possible connection of the concept under study and other mental structures in the situation of assessment. Similarity between the mental structure and a synergetic self-developing system is also pointed out. This is possible due to the equivalent parameters of the concept of assessment and self-organizing non linear, dissipative synergetic system flexible to changes in the process of evolution.